Community health care workers in pursuit of TB: Discourses and dilemmas. (February 2020) - Onazi, Olajumoke; Adejumo, Adedeji Olusola; Redwood, Lisa; Okorie, Onuka; Lawal, Oyewole; Azuogu, Benedict; Gidado, Mustapha; Daniel, Olusoji James; Mitchell, Ellen M.H.
Abstract: Community-led tuberculosis (TB) active case finding is widely promoted, heavily funded, but many efforts fail to meet expectations. The underlying reasons why TB symptom screening programs underperform are poorly understood. This study examines Nigerian stakeholders' insights to characterize the mechanisms, enabling structures and influences that lead programs to succeed or fail. Eight focus group discussions were held with Community Health Workers (CWs) from four models of community-based TB screening and referral. In-depth interviews were conducted with 2 State TB program managers, 8 Community based organizations (CBOs), and 6 state TB and Leprosy Local Government supervisors. Transcripts were coded using Framework Analysis to assess how divergent understandings of CWs' roles, expectations, as well as design, political and structural factors contributed to the observed underperformance. Altruism, religious faith, passion, and commitment to the health and well-being of their communities were reasons CWs gave for starting TB symptom screening and referral. Yet politicized or donor-driven CWs' selection processes at times yielded implementers without a firm grounding in TB or the social, cultural, and physical terrain. CWs encountered suspicion, stigma, and hostility in both health facilities and communities. As the interface between the TB program and communities, CWs often bore the brunt of frustrations with inadequate TB services and CBO/iNGO collaboration. Some CWs expended their own social and financial capital to cover gaps in the active case finding (ACF) programs and public health services or curtailed their screening activities. Effective community-led TB active case finding is challenging to design, implement and sustain. Contrary to conventional wisdom, CWs did not experience it as inherently empowering. Sustainable, supportive models that combine meaningful engagement for communities with effective program stewardship and governance are needed. Crucially effective and successful implementation of community-based TB screening and referral requires a functional public health system to which to refer. Highlights: Altruism and passion were reasons community workers started TB symptom referral. The selection processes of community workers were often politicized. Community workers encountered stigma in health facilities and communities. Lack of training, supervision, necessary equipment, and funds were challenges. Some CWs saw themselves more as exploited workers than as volunteers.